The Influence of Tax Understanding, Tax Awareness and Tax Amnesty toward Taxpayer Compliance - Nurkhin, Ahmad; Novanty, Ine; Muhsin, Muhsin; Sumiadji, Sumiadji (University of Merdeka Malang, 2018)
Taxpayer compliance is still an interesting topic to study since the government has launched tax amnesty program. This study aims at examining the influence of tax understanding, tax awareness and tax amnesty perceptions toward taxpayers’ compliance in East Semarang Pratama Tax Office, Semarang City, Central Java. The research population is taxpayers that are registered in East Semarang Pratama Tax Office. This study used convenience sampling as a sampling technique. This study used 200 (samples) units. Data collection technique used in this research is questionnaire which is developed from some previous studies. The writer then used descriptive statistical analysis and multiple linear regression analysis as the analysis method. The results of this study showed that the understanding of tax, taxpayer awareness and the perception of tax amnesty proved to have a positive and significant effect on taxpayer compliance. The taxpayer understanding and awareness become variables that have a stronger influence than a variable of tax amnesty perception. The other results indicate that gender can influence taxpayer compliance as well. Female taxpayers are more compliant than male taxpayers. It is then suggested that the tax office always enforce tax education programs to taxpayers regularly and continuously to increase the taxpayers’ understanding and awareness.JEL Classification: H23; H26DOI: https://doi.org/10.26905/jkdp.v22i2.1678